Reproductive outcomes of Ongole crossbred cows in the Mapanget District of Manado, North Sulawesi Province - Lapian, H.F.N.; Pudjihastuti, E.; Kaunang, C.L. (Universitas Sam Ratulangi, 2025)
The livestock sector is actually an important contributor to the improvement of the Indonesian economy because it is a source of income for millions of farmers throughout the country. However, in various regions in Indonesia, including in Mapanget District, Manado City, North Sulawesi Province, because traditional livestock practices are still dominant, there are limitations to increase livestock production. Efforts to increase production can be made through intensive observation of the reproductive appearance of traditional locally raised heifers. This study aims to evaluate the reproductive performance of Ongole-crossbreed cow in the Mapanget District The research methodology employed a survey approach, collecting both primary and secondary data. Primary data were obtained directly through interviews with farmers (respondents) using structured questionnaires, while secondary data were sourced from various relevant institutions, including the Animal Husbandry Office, the Sub-District Office, and the Statistics Office. The findings indicate that the reproductive performance of Ongole crossbreed cows in the villages of Bengkol, Buha, and West Mapanget, within the Mapanget District, is favorable. Key reproductive metrics include an average age at puberty of 21 to 24.8 months, a service per conception rate of approximately two, a calving interval of 11.5 to 13.4 months, and an age at first calving ranging from 30 to 33.6 months.